Youth’s Depression of an Artist Portrayed in “Lonely”Song by Justin Bieber - Mursalim, Mufida Julia; Mustikawati, Yunitari (ELITERATE : Journal of English Linguistics and Literature Studies, 2022)
The aims of this study are to analyze the messages in the song "Lonely" and the factors that make Justin Bieber depressed portrayed in "Lonely" by Justin Bieber using psychological approach with the theoryof Edward Bibring;The Mechanism of Depression(2018) and of Aaron Beck;Cognitive Theory of Depression(2009). The historical background of Bieber’s mental health has been examined based onarticles from newspapers or magazines, Bieber’s official Instagram, and Justin Bieber’s Youtubedocumentary. The researchers used the qualitative descriptive method in conducting this research.Researchers found three messages in "Lonely" by Bieber based on data provided by Bieber. There areexpressions of despair and helplessness and struggles of life with fame. Based on the data above,researchers found four factors that made Bieber depressed. Those are substance abuse (drugs), abusiverelationships (emotionally and physically), Lyme disease, and irresponsible behavior.